Misconceptions and Scaffolding Students in Solving Algebraic Operation Problems in Terms of Cognitive Style - Erisca Lusy Rusdianti; Masriyah Masriyah (Prodi Pendidikan matematika Universitas Islam Majapahit (UNIM), Mojokerto, Indonesia, 2021)
Purpose of the research is to describe the types and causes of student misconceptions with field dependent and field independent cognitive styles. As well as providing scaffolding which is used to reduce student misconceptions in solving algebraic operation problems. This research is a qualitative research and was conducted by selecting 2 students of UPT SMPN 33 Gresik who experienced misconceptions with field dependent and field independent cognitive styles. The instruments used were the first and second misconception diagnostic tests which were equipped with CRI, interview guidelines and scaffolding guidelines. The results showed that students with field dependent and field independent cognitive styles experienced classificational, theoretical and correlational misconceptions. The cause of the misconception is the condition of students, students' abilities and books. After being given scaffolding, students with a field dependent cognitive style can solve the questions given and the misconceptions that occur are reduced. As well as misconceptions in students with an independent field cognitive style can be reduced and the process is more systematic. It can be said that giving scaffolding can reduce students' misconceptions in solving algebraic operation problems in students with field dependent and field independent cognitive styles. Keywords: misconception; scaffolding; cognitive style; algebra.